Flavonoids as Promising Akt1 Inhibitors in Cancer Medicine: Insights From Molecular Docking, Dynamics, DFT Calculations, and In Vitro Validation - Shokoofeh Jamshidi; Ali Eghbalian; Setareh Shojaei; Amir Taherkhani; Mehran Feizi‐Dehnayebi (Cancer Reports)
ABSTRACT Background The PI3K/Akt/mTOR signaling pathway is commonly deregulated in different types of cancers, contributing to tumor proliferation, persistence, and resistance to treatment. Akt1, a crucial kinase within this pathway, plays a critical role in tumor progression and the occurrence of therapeutic resistance. The emergence of resistance is a significant challenge in cancer therapy. Targeted therapies offer a promising method to overcome this challenge. Akt1 presents a promising target for therapeutic intervention. Aims This study aimed to evaluate the binding affinities of 61 flavonoid‐derived natural compounds to the Akt1 ATP‐binding site using molecular docking with AutoDock to identify potential Akt1 inhibitors. Methods Cross‐validation and Density Functional Theory analysis were conducted utilizing the SwissDock server and the Gaussian 09 W software suite for the top‐ranked compounds. Following energy minimization, semi‐flexible docking of flavonoids and the control inhibitor Ipatasertib was performed against the Akt1 ATP‐binding pocket. Binding modes were analyzed using Discovery Studio Visualizer. Molecular dynamics simulations were conducted to assess the conformational stability and binding durability of the highest‐scoring Akt1 inhibitor complex identified through molecular docking analyses. The pharmacokinetics and toxicity properties of the most potent Akt1 inhibitors were evaluated using the PreADMET tool. Also, the effect of the most potent Akt1 inhibitor on cell viability was studied in vitro through the 2,5‐diphenyl‐2H‐tetrazolium bromide approach. Besides, the most promising compound was evaluated for its impact against the FOXO3 (an Akt1 downstream target) gene expression in MCF‐7 cells. Results Kaempferol 3‐rutinoside‐4′‐glucoside and Kaempferol 3‐rutinoside‐7‐sophoroside displayed exceptional binding affinities (ΔGbinding = −21.79 and −20.73 kcal/mol; Ki = 106.03 aM and 640.24 aM), surpassing Ipatasertib (ΔGbinding = −9.98 kcal/mol; Ki = 48.29 nM). Kaempferol 3‐rutinoside‐4′‐glucoside achieved a stable binding conformation within the Akt1 catalytic domain after 30 ns of molecular dynamics simulation. The compound Kaempferol 3‐rutinoside‐4′‐glucoside was observed to suppress cell proliferation in MCF‐7 cell lines. This effect was accompanied by an upregulation of FOXO3 expression, suggesting a connection to the induction of the apoptosis pathway. Conclusions Computational analyses identified flavonoids, particularly Kaempferol glycosides, as potential Akt1 inhibitors with significantly higher predicted binding affinities than Ipatasertib. These findings warrant further exploration of the therapeutic potential of flavonoids for cancers driven by Akt1 hyperactivation.